GAMBARAN TINGKAT KECEMASAN MAHASISWA NERS DI SURAKARTA: GAMBARAN TINGKAT KECEMASAN MAHASISWA NERS DI SURAKARTA - Tina Ramadhania; Ida Nur Imamah (Universitas Duta Bangsa Surakarta, 2023)
Introduction: Nursing is a profession that focuses on the care of individuals, families and communities. There are duties, a new clinical environment and UKOM regulations. Therefore, students are required to be able to pass in terms of knowledge and skills so that they become stressors that cause anxiety in students. Objectives: This study aims to knowing the Anxiety Levels of Nurse Students at Surakarta. Methods: Quantitative research with descriptive correlational research design with cross sectional design, the sample taken is 77 respondents with simple random sampling. The research instrument using the HARS (Hamilton Anxiety Rating Scale) questionnaires for anxiety levels. Data analysis was carried out using the descripsion analysis. Results: The results of statistical tests on respondents showed majority of moderate anxiety was 36 students (42.2%). While mild anxiety was 35 students (41.1%), severe anxiety was 14 students (16.5%). The characteristics of the majority of respondents aged 17-25 years are 85 students (100%) and the majority are female 75 students (88.2%). Conclusions: There is a significant description of anxiety level of ners students at Surakarta experiencing anxiety at a moderate level of anxiety.